Robust finite-time estimation of biased sinusoidal signals: a volterra operators approach - Parisini,T; Pin,G; Chen,B (Automatica, 2017)
A novel finite-time convergent estimation technique is proposed for identifying the amplitude, frequency and phase of abiasedsinusoidal signal. Resorting to Volterra integral operators with suitably designed kernels, the measured signal is processedyielding a set of auxiliary signals in which the influence of the unknown initial conditions is removed. A second-order slidingmode-based adaptation law – fed by the aforementioned auxiliary signals – is designed for finite-time estimation of the frequency,amplitude, and phase. The worst case behavior of the proposed algorithm in presence of the bounded additive disturbancesis fully characterized by Input-to-State Stability arguments. The effectiveness of the estimation technique is evaluated andcompared with other existing tools via extensive numericalsimulations.